Case Report of Phacolytic Glaucoma in the Eye Department of Dr. M. Djamil Hospital Padang - Fitria Rahmi Nukti; Fitratul Ilahi (International Journal of Health and Social Behavior, 2024)
A 68-year-old man came to the polyclinic at a type A hospital in West Sumatra with complaints of pain in the right eye since 3 weeks before coming to the hospital. Anamnesis and physical examination were performed on the patient and a diagnosis of phacolytic glaucoma was established. This article aims to report a case of phacolytic glaucoma which is a rare case of secondary open-angle glaucoma.